Sum

Calculus Level 2

n = 0 2 n + 3 n n ! = ? \large \sum _{ n=0 }^{ \infty }{ \frac { { 2 }^{ n }+{ 3 }^{ n } }{ n! } } = \, ?

1 e 2 + e 3 { e }^{ 2 }+{ e }^{ 3 } e 2 + e { e }^{ 2 }+{ e } e 5 { e }^{ 5}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

We have e x = n = 0 x n n ! \large e^x=\sum_{n=0}^{\infty} \frac{x^n}{n!} , n = 0 2 n + 3 n n ! = n = 0 2 n n ! + n = 0 3 n n ! = e 2 + e 3 \large \sum _{ n=0 }^{ \infty }{ \frac { { 2 }^{ n }+{ 3 }^{ n } }{ n! } } = \sum_{n=0}^{\infty} \frac{2^n}{n!} + \sum_{n=0}^{\infty} \frac{3^n}{n!} = e^2+e^3

Nice solution

Jun Arro Estrella - 5 years, 1 month ago

For series representation e 2 ( 1 + e ) = ( k = 0 1 + k + z k ! ) 2 ( z + k = 0 1 + k + z k ! ) z 3 e^2(1+e)=\dfrac{\left(\sum_{k=0}^{\infty} \dfrac{-1+k+z}{k!}\right)^2\left(z+\sum_{k=0}^{\infty}\dfrac{-1+k+z}{k!}\right)}{z^3}

Partial sum formula:

n m 2 n + 3 n n ! = e 2 ( Γ ( m + 1 , 2 ) + e Γ ( m + 1 , 3 ) ) Γ ( m + 1 ) \sum_{n}^{m}\frac{2^n+3^n}{n!} = \frac{e^2(\Gamma(m+1,2)+e\Gamma(m+1,3))}{\Gamma(m+1)}

ADIOS!!! \LARGE \text{ADIOS!!!}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...